BUDAYA ORGANISASI SYCHOPANCY TERHADAP MODEL POLITIK ORGANISASI CLIENTELISME PNS NAGAN RAYA - Ranti; Rahmat Hidayat, Muhammad; Rusdi (Sebi : Studi Ekonomi dan Bisnis Islam, 2025)
This study focuses on investigating the relationship between the organizational culture of sycophancy and the organizational political model of clientelism among civil servants (PNS) in Nagan Raya. The sampling method applied in this research is stratified random sampling, with a total sample size of 257 civil servants from Nagan Raya. Data collection was conducted through a survey technique using a questionnaire as the data collection instrument. Data analysis was performed using a simple regression model calculated through the SPSS 24 software. The findings reveal that the organizational culture of sycophancy influences the organizational political model of clientelism among civil servants in Nagan Raya, as evidenced by a calculated t-value (t-count) of 12.020, which is greater than the critical t-value (t-table) of 1.650. The independent variable in this study explains 35.9% of its influence on the dependent variable.